2007
DOI: 10.1111/j.1365-2222.2007.02874.x
|View full text |Cite
|
Sign up to set email alerts
|

TBXA2R gene polymorphism and responsiveness to leukotriene receptor antagonist in children with asthma

Abstract: A combined effect of TBXA2R+795T>C and +924T>C risk alleles may be linked to IgE production, eosinophilic inflammation, and severity of asthma. In addition, the TBXA2R+795T>C genotype may be a predictive marker of a clinical response to the LTRA in Korean asthmatic children with EIB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…In these populations, polymorphisms in TBXA2R have been associated with asthma, atopy, asprin sensitivity, and blood levels of specific IgE (Ober and Hoffjan 2006;Kim et al 2008). We provide evidence demonstrating that TBXA2R is associated with both atopy and AHR in Caucasians ( Table 2).…”
Section: Discussionmentioning
confidence: 66%
“…In these populations, polymorphisms in TBXA2R have been associated with asthma, atopy, asprin sensitivity, and blood levels of specific IgE (Ober and Hoffjan 2006;Kim et al 2008). We provide evidence demonstrating that TBXA2R is associated with both atopy and AHR in Caucasians ( Table 2).…”
Section: Discussionmentioning
confidence: 66%
“…Conflicting results about the genetic alteration of TBXA2R in the involvement of asthma have been reported in an Asian population (13)(14)(15). Genetic alteration of CRTH2 has been correlated to allergic asthma in African-American and Chinese populations (18), but not in a Japanese population (19).…”
Section: Discussionmentioning
confidence: 97%
“…TBXA 2 exerts its action, such as bronchoconstriction and bronchial hyper responsiveness (10,11), by interacting with the G protein- (13) showed a positive association between the TBXA2R polymorphism and the development of atopy and asthma. On the other hand, Kim et al (14) showed that the TBXA2R polymorphism was not associated with asthma susceptibility and the clinical parameters of asthma. In a Japanese population, Unoki et al (15) found that the synonymous +924T>C polymorphism in the TBXA2R gene was associated with a diagnosis of asthma in adult asthmatic patients, but not in children.…”
Section: Introductionmentioning
confidence: 99%
“…Trials of montelukast have provided variable results [45][46][47][48]. In one trial, montelukast provided measurable protection against EIB in asthma patients 15 to 44 years of age, with onset of action within 2 hours [46].…”
Section: Therapymentioning
confidence: 97%